2015
DOI: 10.1039/c5ta04777c
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell structured BaTiO3@carbon hybrid particles for polymer composites with enhanced dielectric performance

Abstract: Core–shell structured BaTiO3@carbon hybrid particles fabricated via chemical vapor deposition can remarkably enhance the dielectric performance of polymer composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 58 publications
3
54
0
1
Order By: Relevance
“…They used the chemical vapor deposition (CVD) method to grow fewer CNTs on the surface of BT (BT@CNTs), and found that BT@CNTs greatly improve the dielectric properties of poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP). The BT@CNTs/PVDF‐HFP with 10 vol% BT@CNTs had a permittivity of 27.7 at 10 3 Hz, which was 1.65 times higher than the BT/PVDF‐HFP with 10 vol% BT, while the dielectric loss was even lower than pure PVDF‐HFP …”
Section: Cnts/polymer Dielectric Nanocompositesmentioning
confidence: 95%
“…They used the chemical vapor deposition (CVD) method to grow fewer CNTs on the surface of BT (BT@CNTs), and found that BT@CNTs greatly improve the dielectric properties of poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP). The BT@CNTs/PVDF‐HFP with 10 vol% BT@CNTs had a permittivity of 27.7 at 10 3 Hz, which was 1.65 times higher than the BT/PVDF‐HFP with 10 vol% BT, while the dielectric loss was even lower than pure PVDF‐HFP …”
Section: Cnts/polymer Dielectric Nanocompositesmentioning
confidence: 95%
“…One common approach in high-k polymer composites is to incorporate ceramic fillers into a polymer matrix. Poly (vinylidene fluoride) (PVDF) based polymers have been investigated due to higher permittivity than other polymers [7][8][9]. Some high dielectric constant ceramics, such as barium titanate (BT), barium strontium titanate (BST) [9] and calcium copper titanate (CCTO) [10,11] have been used as fillers.…”
Section: Introductionmentioning
confidence: 99%
“…polarization between the PVDF matrix and CCTO@Ni filler, which is the same as the related literature. 16, 35 These results demonstrate that magnetic treatment may significantly enhance the dielectric permittivity of PVDF composites. Figure 7 shows how the magnetic field treatment affected the conductivity of PVDF#1-3 at room temperature.…”
Section: B Dielectric Properties Of Pvdf and The Untreated Pvdf Compmentioning
confidence: 64%
“…[21][22][23] The CCTO sol was produced by adding C 16 The core-shell CCTO ceramic was produced by depositing Ni nanoparticles on CCTO microparticles by electroless plating. 24,25 To clean the microparticles, 8 g of CCTO particles were dispersed by ultrasonication for 30 min in an 80 mL solution of 80 vol.% hydrogen fluoride and water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation